Corporate social responsibility in zones of conflict - Sarah Rieper (Freie Universität Berlin, Center for International Political Economy, 2013)
Departing from the previous focus on negative involvements of business in the political economy of war and its role in fuelling or causing conflict, transnational corporations are increasingly expected to contribute to conflict prevention, crisis management and post-conflict peace building. This paper analyzes under which conditions transnational corporations contribute to peace and security in zones of conflict. The question is explored in the framework of a comparative case study of Shell' engagement in Nigeria and BP's engagement in Azerbaijan. It is argued that transnational civil society activism, company and production characteristics and the role of the host state are crucial determinants of corporate engagement towards peace and security.
urn:nbn:de:101:1-201307223992
Keywords: 330